A novel core@shell magnetic molecular imprinted nanoparticles for selective determination of folic acid in different food samples - Hussain, Sajjad [UNESP]; Khan, Sabir [UNESP]; Gul, Saima; Pividori, Maria Isabel; Del Pilar Taboada Sotomayor, Maria [UNESP] (Elsevier, 2016)
In this work, magnetic molecularly imprinted polymers (MMIPs) were synthesized and tested for the determination of folic acid (FA) in different food samples. The MMIPs were polymerized at the surface of Fe3O4@SiO2 magnetic nanoparticles (MNPs) using acrylonitrile (functional monomer), ethylene glycol dimethacrylate (EGDMA) as cross-linking agent and azobiisobutyronitrile (AIBN) as an radical initiator. The morphological, topological and chemical characteristics of the MMIPs were investigated by field emission scanning electron microscopy (FESEM), high resolution transmission electron microscopy (HRTEM) and Fourier transform infrared (FTIR) techniques. The physico-chemical characterization, such as adsorption capacities and selectivity of MMIPs was investigated and compared with the respective MNIPs. The adsorption experimental data demonstrate that maximum adsorption capacity of MMIP at equilibrium was 8 mg g− 1 and than the adsorption process of FA over MMIPs follows Freundlich adsorption isotherm model and pseudo-first-order reaction kinetic. For evaluation of this new proposed material, the recovery studies were carried out in spiked samples at different concentration levels and the obtained values were in the range of 95–104% for orange and for spinach the recoveries were between 99.5 and 102.5%. The relative standard deviations (RSD) for the recoveries were < 0.5% for both samples. These results demonstrate that this novel MMIP material can be efficiently used for the selective extraction of folic acid from different food complex matrices.
Keywords: Folic acid; Food; Magnetic nanoparticles; Molecularly imprinted polymer